Novel Applications of Mesenchymal Stem Cell-Derived Exosomes for Myocardial Infarction Therapeutics - Sho Joseph Ozaki Tan; Juliana Ferreria Floriano; Laura Nicastro; Costanza Emanueli; Francesco Catapano (Biomolecules, 2020)
Cardiovascular diseases (CVDs) are the leading cause of mortality and morbidity globally, representing approximately a third of all deaths every year. The greater part of these cases is represented by myocardial infarction (MI), or heart attack as it is better known, which occurs when declining blood flow to the heart causes injury to cardiac tissue. Mesenchymal stem cells (MSCs) are multipotent stem cells that represent a promising vector for cell therapies that aim to treat MI due to their potent regenerative effects. However, it remains unclear the extent to which MSC-based therapies are able to induce regeneration in the heart and even less clear the degree to which clinical outcomes could be improved. Exosomes, which are small extracellular vesicles (EVs) known to have implications in intracellular communication, derived from MSCs (MSC-Exos), have recently emerged as a novel cell-free vector that is capable of conferring cardio-protection and regeneration in target cardiac cells. In this review, we assess the current state of research of MSC-Exos in the context of MI. In particular, we place emphasis on the mechanisms of action by which MSC-Exos accomplish their therapeutic effects, along with commentary on the current difficulties faced with exosome research and the ongoing clinical applications of stem-cell derived exosomes in different medical contexts.